3D wide‐field multispectral photoacoustic imaging of human melanomas in vivo: a pilot study. (5th December 2020) - Park, B.; Bang, C.H.; Lee, C.; Han, J.H.; Choi, W.; Kim, J.; Park, G.S.; Rhie, J.W.; Lee, J.H.; Kim, C.
Abstract: Background: The Breslow depth is an important parameter to determine the excision margin and prognosis of melanoma. However, it is difficult to accurately determine the actual Breslow depth before surgery using the existing ocular micrometer and biopsy technique. Objectives: To evaluate the use of 3D wide‐field multispectral photoacoustic imaging to non‐invasively measure depth and outline the boundary of melanomas for optimal surgical margin selection. Methods: Six melanoma patients were examined in vivo using the 3D multispectral photoacoustic imaging system. For five cases of melanomas (one in situ, three nodular, and one acral lentiginous type melanoma), the spectrally unmixed photoacoustic depths were calculated and compared against histopathological depths. Results: Spectrally unmixed photoacoustic depths and histopathological depths match well within a mean absolute error of 0.36 mm. In particular, the measured minimum and maximum depths in the in situ and nodular type of melanoma were 0.6 and 9.1 mm, respectively. In the 3D photoacoustic image of one metastatic melanoma, feeding vessels were visualized in the melanoma, suggesting the neovascularization around the tumour. Conclusions: The 3D multispectral photoacoustic imaging not only provides well‐measured depth and sizes of various types of melanomas, it also visualizes the metastatic type of melanoma. Obtaining accurate depth and boundary information of melanoma before surgery would play a useful role in the complete excision of melanoma during surgery.